Testing for asymmetry in the inflation-unemployment trade-off: some evidence for the USA - St. Aubyn, Miguel (2000)
Two sources of asymmetry in the Phillips curve are considered: the "capacity constraint hypothesis" and downward rigidity on wages and/or prices. The short run trade-off between inflation changes and the unemployment gap is modeled in a state-space framework that allows for time variation in both the NAIRU and the trade-off parameter. Empirical evidence for the US using the Kalman filter favors convexity of the Phillips curve, the trade¬off depending positively on the unemployment gap and on inflation changes. The two sources of asymmetry produce almost equivalent observational models, so it is not possible to distinguish one from the other.